2018
DOI: 10.1002/jbt.22225
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of iron oxide nanoparticles: Size and coating effects

Abstract: Toxicological research of novel nanomaterials is a major developmental step of their clinical approval. Since iron oxide magnetic nanoparticles have a great potential in cancer treatment and diagnostics, the investigation of their toxic properties is very topical. In this paper we synthesized bovine serum albumin‐coated iron oxide nanoparticles with different sizes and their polyethylene glycol derivative. To prove high biocompatibility of obtained nanoparticles the number of in vitro toxicological tests on hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 22 publications
3
59
0
1
Order By: Relevance
“…Similarly, previous studies found correlations between cytotoxicity and the NPs’ hydrodynamic size [ 97 , 98 , 99 , 100 , 101 ]. In most cases, the hydrodynamic size of the NPs is larger than the core size.…”
Section: Resultssupporting
confidence: 71%
“…Similarly, previous studies found correlations between cytotoxicity and the NPs’ hydrodynamic size [ 97 , 98 , 99 , 100 , 101 ]. In most cases, the hydrodynamic size of the NPs is larger than the core size.…”
Section: Resultssupporting
confidence: 71%
“…However, there was no significant difference in bactericidal activity between macrophages with and without AMF application at the same MNP dose (Figure 5(B)), suggesting that exposure of MNPs to the RAW 264.7 macrophages was sufficient enough to exhibit a bactericidal activity against intracellular S. aureus. Since iron oxide magnetic nanoparticles can trigger the generation of ROS [33][34][35], and ROS can exhibit an antimicrobial activity [36], we next examined whether the improved bactericidal activity of macrophages with MNPs alone or MNP/ AMF hyperthermia was associated with increased ROS generation. The generation of intracellular ROS in the RAW 264.7 cells was significantly increased with increasing concentration of MNPs ( Figure 5(C)).…”
Section: Resultsmentioning
confidence: 99%
“…, who verified the influence of IONPs coated with bovine serum albumin (BSA) as well as BSA‐coated and PEGylated on primary human fibroblasts and U251 human glioblastoma cell line. They found that BSA-coated and PEGylated IONPs had the less toxic influence on human fibroblasts and explained this effect by the protective action of PEG‐coating, which prevents the active uptake of NPs and delays their degradation and the release of iron ions 63 . Functionalization of our NPs with PEG might have caused that their negative impact on cell proliferation was usually less than this observed for Fe salts.…”
Section: Discussionmentioning
confidence: 99%